Efeito de diferentes intervenções domiciliares no desenvolvimento de crianças contaminadas por chumbo: um estudo longitudinal - Ribeiro, Máyra (2007)
Lead is a toxic metal that affects all the organs and systems of the human body, being its absorption bigger in children and pregnant women. Although the harmful effect of lead in infantile development (e.g., hyperactivity, cognitive deficit, low efficiency at school, etc) there are no studies on the effect of intervention programs for this population. The objectives of this work were: 1. to compare, the acquisition of abilities (foreseen in the Portage Guide) for children of 3 to 5 years old, with average level of lead equal to 21 g/dl at four moments and 2. to verify the effect of two domiciliary interventions (A: individual training of the mother according to procedures of the Portage Guide, and the other, B: toys and models of tricks available to the child - environmental enrichment) in its performance. Two groups of 4 children were analyzed, being two groups of intervention and one of waiting control. The delineation counts on: evaluation retrospect (2002/03), a pre-test evaluation of all children in Portage Guide and HOME; implementation of the intervention programs with groups A and B (23 sessions); sounding the trained and emergent behaviors (application of the Portage Guide); retaken of the intervention program (9 weeks); post-test 1 (Portage Guide and HOME); post-test 2 (Portage Guide); post-test 3 with only one child of each group; besides the weekly evaluation of the children s performance through observation and record and posterior intervention with the controlled group. The results pointed to a decay of performance in the Portage Guide of evaluation 2002/03 for the pre-test, in the three groups, being the greater deficits in the cognition and language areas. After the period of intervention, children from group A got greater addition of behaviors, followed by group B and finally group C. The environment quality and care of these children came to be insufficient, but with improvements to the intervention for the submitted groups. It can be concluded that the two interventions speed up the development, but with better results for the intervention with parents guiding. The results indicate, also, that deficits of behavior tend to extend themselves throughout the time when it comes to this population.